You are on page 1of 28

# -

IIIIIIIV

III

IIIIV

AB B A

41

I4

1.
1.1

1.2 1.2

1.3

2. 2.1

2.2

1. 1.1

1.2
1.3 1.3

2. 2.1 2.1

3. 3.1
3.1
n

3.2 a

3.3

4. 4.1 4.1

1.
1.1

2.
2.1

3.
3.1
3.2
3.2

4.
4.1

5. 5.1 5.1

42

5.2
5.3
5.4

43

II
4

1.
1.1

1.2

1.1

1.2

/ I

2.
2.1
1. 1.1

1.2

1.3

1.4

2.
2.1
2.1
2.2

3.
3.1 3.1

1. 1.1

2. 2.1
2.1

3. 3.1

1. 1.1 1.1

2. 2.1 2.1

1.

2.

44

III
4

1. 1.1

2. 2.1 2.1

2.2
3. 3.1

4.
4.1 4.1

5.
5.1
5.1
5.2
1. 1.1

1.2

2.
2.1
2.2

3. 3.1

3.2 3.2

1. 1.1

1.2

2. 2.1

2.2

3. 3.1

3.2

## cot, sec, csc

I
I

45

IV4

1.
1.1 1.1

2. 2.1

2.2

3. 3.1

4. 4.1

4.2

4.3 4.3

1.
1.1

2. 2.1

2.2

3. 3.1

3.2

1. 1.1 1.1

2.
2.1

3.
3.1
4. 4.1
4.2
4.2

1.
1.1

2.
2.1

3.
3.1

46

1.

2.
3.
4.

5.

1
2
3
6.

7.

8.

47

IIIIII IV

48

1.
1.1

1.2

1
= 2 + 1 a 2 = a
2 1

a+b

1.3

ab

( a + b ) ( a + b ) ( a 2 ab + b2 ) ( a b ) ( a 2 + ab + b2 ) ( a + b + c )
2

(1 x ) (1 + x + x 2 )
( x + y 1)( x y + 2 )

x3 + y 3 + z 3 3 xyz = ( x + y + z )( x 2 + y 2 + z 2 xy yz zx)

c
1
2ab
1
=

5+ 2 6 = 3 + 2
=
2
2
2
2
11 1 a +b
a
+
b
a b
+
+
2a b
c c

x 2 + x 2 + 2 = x + x 1
2.
2.1
a, b a, b 2:3 x
2.2
a + b a + b
x 3 < 2 x 1 < 1 1 < x < 2
x 1 < 2 x 3

49

y = cx n n=1234

(x a )(x a ) (x b )x 2 + 1x 2 + x + 1 f (x )
(x a ) f ( a ) (x a ) f ( x ) (x a )

f ( x ) a f (x ) (x a ) ( x b )
(a, ) (b, ) f (x )
(x a ) ( x b )

1.
1.1
y = f ( x )
y = mx + b = m ( x x0 ) m, x0 , b m
y x
1.2
f ( x) = x 2 + 2 x + 3,2 x 2
50

x 2 x + 4

y = c ( x a )( x b )

y = ax 2 + bx + c y = a ( x h ) + k
2

1.3
y = x n n = 1, 2, 3, 4 [ 1.5,1.5]

n y = cx n
c y = cx n
y = c ( x h ) + k
n

2.

2.1

( x a ) ( x n 1 + x n 2 a + L + a n 1 ) = x n a n n = 2,3,4

( x + a )( x 2 ax + a 2 ) = x 3 + a 3

f ( x ) = 2 x 3 5 x 2 + 6 x + 3 = a + b ( x 1) + c ( x 1) + d ( x 1) a, b, c, d
2

f (1.01)

f ( x ) = 2 x 3 5 x 2 + 6 x + 3 = a + b ( x 1) + c ( x 1)( x 2 ) + d ( x 1)( x 2 )( x 3)
a, b, c, d

f ( x ) (x a ) ( x b ) ( a, f ( a ) ) , ( b, f ( b ) )
f a,b f f ( x ) = q ( x )( x a )( x b )

(1,1) , ( 2, 3) , ( 3, 7 ) f ( x ) = a + b ( x 1) + c ( x 1) ( x 2 )

1
a, b, c f
2

51

## (11,3), (12,5), (13,8)

( x 12)( x 13)
( x 11)( x 13)
( x 11)( x 12)
f ( x) = 3
+ 5
+ 8
(11 12)(11 13)
(12 11)(12 13)
(13 11)(13 12)
f (11.5)

(1,1) , ( 2, 3) , ( 3, 7 )

f ( x ) = a + bx + cx 2
a, b, c IV

3.
3.1

ax 2 + bx + c = 0

x 2 + 5 x + 3 = 0 2 + 2 3 + 3
1
1
3

+
=
x 1 x 2 2
n
3.2 a

x n = a a>0 f ( x ) = x 3 + 2 x 2 + 3 x + 4

n
3.3

f ( x ) = k ( x a1 ) 1 L ( x ak ) k ( x 2 + b1 x + c1 ) L ( x 2 + bm x + cm )
r

s1

sm

f ( x ) = 5 x 4 21x 3 + 30 x 2 9 x + 7 x = 2 + i

4.
4.1

( x 1)( x + 2 )

( x 4 ) > 0 ( x 1)( x 2 )

x3 1 > 0 x4 2 x2 3 > 0

52

(x

+ x + 1) > 0

1
1
1
< 1 < 1
< 0
x
x 1
x

10 x , x = 0.1,0.2,L ,0.9

a > 0, a 1

2 x 10 x
x = log a b a x = b
10

## log( xy ) = log x + log y

log ( x / y ) = log x log y log x = log x

( )

1
10 log a x =
log x
log a
y = log x y = log x

1.
1.1
1

n 10 2 10 3 = 10 6 2 3 33 = 6 3
1

10 3 < 10 2

( x a b ) c a ( x b c ) a b ( x c a ) b c
a 3 x + a 3 x
a = 2 + 3 x

a + a x + 6

2x

53

2.
2.1
2 x
10 x
3.
3.1
log( xy ) = log x + log y log ( x / y ) = log x log y

( )

log x = log x
n
log a b, ( log a b )( log b c ) = log a c, a log x b = blog x a
m
1
3.2 log a x =
log x
log a
10

4.
4.1

y = a x x = log a y
1
log a x = log x = log a
log a m bn =

log a + log b
a+b
a +b

log
a = b
2
2
2

5.
5.1

5.2
ab

2100 (1.18 )
10

5.3

5.4

54

II

1.
1.1

an +1 = an + d an +1 = ran an +1 = an + n an +1 = an + n 2 an +1 = ( n + 1) an

1.2
/ II
2.
2.1

k =1

k =1

k =1

k =1

( ak + bk ) = ak + bk cak = c ak
k =1

n +1

k =1

k =2

ak = ak 1
n

k =1

k =1

k =1 k ( k + 1)

k k 2

1.
1.1
55

1.2

1.3
|S| S

10 8 3 5 7 21 4 1
10+8+3+5+7+21+4+1+3+6 = 68

51

51

50

1.4
A B |A B| = |A| + |B|
A, B A B |A B| = |A||B|
A, B, C
1 |A B| = |A| + |B| |A B|
2 |A B C| = |A| + |B| + |C| |A B| |B C| |C A| + |A B C|

## Principle of Inclusion and Exclusion PIE

Inclusion and
Exclusion PIE
2.
2.1

n n!
1 n 1 n
n!
n k
56

n!
1 k 1 n
(n k )!
Pkn
50 1

n k
nk
1 k 1 n
nk
10 103
1 0 A={0,1} n
An = A A . . . A n 2n
2.2
n!
Ckn =

k !( n k )!

n k
n!
Ckn =

k !( n k )!
k 1 n
Ckn

n k
C n + k 1
k
Pkn =

k 1 n
Ckn + k 1
n k x1 + x2 + + xn = k
Ckn + k 1
3.

3.1
(x + yn
5

x 2 + + 1
x

57

1.
1.1

3
2.
2.1

50
3.
3.1
ABC A 40%B
30%C 30% A 5%B
10%C 8%
A

90%
90%
90% 2%

1.
1.1
1
1 n

= xk ( x1 x2 L xn ) n
n k =1

xi

1 n
2
( xk )

n k =1

1 n
2
( xk x ) 2 x=

n k =1

xi

58

2.
2.1
0

## ( xk , y k ) , k = 1, 2,L , n , e(r ) = y k rxk

n

k =1

n
n

2
2
r e(r ) = y i 2 xi y i r + xi r 2 = nr 2 2 xi y i r + n
i =1

i =1
n
1
r = x i y i
n i =1
y = rx e( r)

II

1.

2.

III

59

360 r 0 360

1.
1.1

60

2.
2.1

X
= 150, = 30; = 225, = 45; = 300, = 60

cos , sin

2.2
r, 0 r < , 0 < 360
3.

C
BC = CD + BD = b 2 sin 2 A + ( c b cos A)
2

= b 2 + c 2 2bc cos A

A
D
B

ABC B ( c, 0 ) C

( b cos A, b sin A)
1
ABC c b sin A
2
1
ABC a c sin B
2
1
ABC a b sin C
2
ABC A B ( c, 0 ) C
( b cos A, b sin A)

2

## 4. cos ( 2 1 ) = cos 1 cos 2 + sin 1 sin 2

4.1

B ( cos 2 ,sin 2 )

A,B
A ( cos 1 ,sin 1 )
( cos 1,sin 1 ) , ( cos 2 ,sin 2 )
OAB
cos ( 2 1 ) = cos 1 cos 2 + sin 1 sin 2

61

1,0

## cos (1 + 2 )sin (1 + 2 ) tan (1 + 2 ) cos 2

sin 2 cos

sin

cos15o
5.

5.1

5.2

1.
1.1

1.2

2.
2.1

2.2
ax + by = k
3.
3.1
3.2

62

v v
a b
v v
a b cos = a1b1 + a2 b2
v v
a b sin = a1b2 a2 b1

a x + b1 y = c 1
1

a2 x + b2 y = c2
v
v
v
v v
c = xa + yb a b 0
v v
a b
1.
1.1

1.2

2
x + y 0 x 1 , 0 y 1
1
2

1 2
4

5
2 1
2.
2.1

63

r
r
a = ( a1 , a2 ) , b = ( b1 , b2 )

( b1 , b2 )

r2 r2
r r
( a1 b1 ) + ( a2 b2 ) = a + b 2 a b cos
r r
a1b1 + a2b2 = a b cos
2

r
b

r r
r r
a, b a b

r r r r
r r r r r r r r r r2
a b = ba a + b c = a c + bc a a = a

r
a

( a1 , a2 )

ax + by ( a 2 + b 2 )( x 2 + y 2 )
r r r r
a + b a + b
2

4, 51, 2

2.2
3.
3.1

1OABO0,0 A ( a1 , a2 ) B ( b1 , b2 )
y
B ( b1 , b2 )

A ( a1 , a2 )

OAB =
=

1
1
1
b1b2 + ( a2 + b2 )( a1 b1 ) a1a2
2
2
2

1
( a1b2 a2 b1 )
2

x
D
C
r r
2 a, b
1 v v
1 v v
1 v2 v2 v v 2
OAB = a b sin = a b 1 cos2 =
a b a b
2
2
2

1
1
2
2
2
2
2
=
( a1 + a2 )( b1 + b2 ) ( a1b1 + a2b2 ) = 2 a1b2 a2b1
2
a b
a a
b a1
a + c b1 a1 b1 c1
1 1 = 1 2 = 1
1 1
=
+
a2 b2 b1 b2
b2 a2
a2 + c2 b2 a2 b2 c2

ca1
ca2

b1
a
=c 1
b2
a2

b1

b2

64

b1
b2

3.2
a x + b1 y = c 1
1

a2 x + b2 y = c2
v
v v
v v
c a b a b
0

IV

0
0
1.
1.1
2.
2.1
2.2

## {s (1, 2,3) + t ( 0,1, 1) | 0 s 1,0 t 2}

3.
3.1
( a1 , a2 , a3 ) ( b1 , b2 , b3 )
v v
v v
a1b1 + a2b2 + a3b3 = a b cos a b a1b1 + a2b2 + a3b3

4.
4.1

65

v v
v v
A =| a |2 | b |2 a b

a
= 2
b2

a3
a
+ 3
b3
b3

a1
a
+ 1
b1
b1

a2

b2

4.2

v v v
v v v
a , b , c a (b c )
4.3

a2 + 1

ab
ac
b+c

a+c

a+b

ba

ca

b2 + 1

cb

bc

c2 + 1

1.
1.1
2.
2.1

x 1
z
L :
= y + 1 = E : 2 x + y z = 3
2
3
2.2
3.
3.1

3.2
a1 x + b1 y + c1 z = d1

a2 x + b2 y + c2 z = d 2
a x + b y + c z = d
3
3
3
3

v v v
uv
v v v
d a b c a b c
0

66

1.

2.
2.1
Caley-Hamilton

3.
3.1

4.
4.1
4.2

1 2
1 2
1 0
A =
A

2 1
2 1
0 1
1 2
1 3

2 1
2 4

67

1.
1.1
2

x 2 + ( y - c ) = y + c

2.
2.1

( x c)

+ y2 +

( x + c)

+ y 2 = 2a

x = x h
( x h ) + ( y k ) = 1 x 2 + y 2 = 1

a2
b2
a 2 b2
y = y k

x2 y2
+
= k
a 2 b2
x
y
x2 y2
x2 y2
x = , y = 2 + 2 = t 2 2 + 2 = 1
a
b
a
b
t
t

ax 2 + cy 2 + dx + ey + f = 0
2

a ( x h ) + c ( y k ) = ah 2 + ck 2 f
2

3.
3.1

( x c)

+ y2

( x + c)

+ y 2 = 2a

68